Active `juvenile' cirrhosis considered as part of a systemic disease and the effect of corticosteroid therapy. Issue 4 (December 1963) - Read, A. E.; Sherlock, Sheila; Harrison, C. V.
Abstract : This is a clinical study of 81 patients (32 male and 49 female), who are not alcoholics, with jaundice of hepato-cellular type lasting longer than three months. Forty-nine of these patients were under 21 years of age. The natural history of the condition and the response to corticosteroid therapy is described; good symptomatic relief can be achieved with corticosteroids but they do not seem to prolong life. The aetiology is discussed with special reference to the relationship to viral hepatitis, to systemic lupus erythematosus, and to other disturbances of immunity.